1997
DOI: 10.2307/3433544
|View full text |Cite
|
Sign up to set email alerts
|

Cell Size of Alveolar Macrophages: An Interspecies Comparison

Abstract: Alveolar macrophages (AM) play a critical role in the removal of inhaled particles or fibers from the lung. Species differences in AM size may affect the number and size range of particles/fibers that can be actually phagocytized and cleared by AM. The purpose of this study was to compare the cell size of rat, hamster, monkey, and human AM by selective flow cytometric analysis of cell volume. Resident AM from CD rats, Syrian golden hamsters, cynomolgus monkeys, and nonsmoking, healthy human volunteers were har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 2 publications
6
53
0
Order By: Relevance
“…Alcohol-fixed FNAC smears are therefore better suited than histological sections to perform such an assessment. The average reported diameter of monocyte/macrophages and alveolar macrophages is 15-30 µm and 21.2 µm, respectively [36,37]. In our study, the mean nuclear diameter of histiocytes of reactive lymph nodes was significantly smaller than that of RDD histiocytes (10.1 vs. 16.7 µm, p < 0.01).…”
Section: Discussionsupporting
confidence: 44%
“…Alcohol-fixed FNAC smears are therefore better suited than histological sections to perform such an assessment. The average reported diameter of monocyte/macrophages and alveolar macrophages is 15-30 µm and 21.2 µm, respectively [36,37]. In our study, the mean nuclear diameter of histiocytes of reactive lymph nodes was significantly smaller than that of RDD histiocytes (10.1 vs. 16.7 µm, p < 0.01).…”
Section: Discussionsupporting
confidence: 44%
“…Coarse particles, such as those resulting from ore crushing and grinding, deposit in the upper respiratory system and are swallowed and go through the digestive system where contaminants may be absorbed, depending on their bioavailability. In contrast, fine particles, such as those originating from smelting operations, are respired deep into the lungs where they can be transported directly to the blood stream (Krombach et al, 1997; Park and Wexler, 2008; Valiulis et al, 2008). In addition, dermal deposition and incidental ingestion are exposure mechanisms that are related to particle size.…”
Section: Mining and Smelting Operations And Environmental Assessmentmentioning
confidence: 99%
“…From a study on the bioavailability of Pb according to size fraction from ambient aerosols around a Pb smelter, Spear et al (1998) found that not only was the highest percentage of Pb concentration in the fine size fraction, but also it contained the largest percentage of bio-available Pb. Therefore, finer size fraction particles that deposit in the lungs and are transported to the blood stream via macrophages have a higher bioavailability (Krombach et al, 1997) and have been shown to contain the largest concentrations of metals and metalloids from smelter emissions (Spear et al, 1998; Csavina et al, 2011). …”
Section: Health and Environmental Impactsmentioning
confidence: 99%
“…When reaching the lungs, such particles can then be transported to the blood stream by macrophages while contaminants such as metals and metalloids can diffuse into the blood stream 26-27 .…”
Section: Introductionmentioning
confidence: 99%